Tỷ suất sinh lời ngày đầu tiên đối với các thương vụ phát hành cổ phiếu lần đầu ra công chúng (IPO) của các nhà đầu tư tại Việt Nam - Nguyễn Văn Tân; Trịnh Quốc Trung; Ninh Thị Trang (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2019)
The study aims to provide empirical evidence on first-day excess return for IPO investment of investors in Vietnam, along with determining factors affecting abnormal first-day return for IPOs in Vietnam. With the selection of 167 enterprises that conducted initial public offerings in Vietnam from 2005 to 2016, the authors conclude that abnormal first-day return of investors in the IPO reached 33.30% for ARi (Abnormal First-Day Return) and reached 23.91% for MAARi1 (Market-Adjusted Abnormal Returns) on average. Besides, the research results also show that abnormal first-day return for IPO investment is not the same among sectors, firm size, and pre and post economic crisis in 2008. This research applies the Bayesian model average method. The results show that factors affecting short term return for IPO investment include IPO offer price, and state ownership rate within one year after IPO.
Keywords: Equitization; Initial public offerings; Regression method; Initial excess return; Underpricing; State-owned enterprises